The Motion of Solar Wind Charged Particle in a Sinusoidal Vibrating Magnetic Field - Iratius Radiman (Institut Teknologi Bandung, 2007)
The motion of solar wind charged particle in a small perturbed magnetic field lines of magnitude B1 is derived througha perturbed Lorentz force. By introducing a small sinusoidal velocity perturbation v1 in transverse direction to theoriginal velocity field vo, a small perturbed magnetic field is resulted from the original magnetic field of magnitude B0. Asystem of simultaneous differential equations describing the perturbed Lorentz force in Cartesian coordinates isobtained. These equations, denoted as RESY, are then treated numerically to follow qualitatively the behaviour of thecharge motion locally. The squared space velocity resulted from RESY are twice to three times larger than the initialvelocity squared in the case of constant magnetic field. Here the initial velocity was normalized to unity,whereas itsvalue may be estimated from the well-known Parker exponentially increased solar-wind velocity. Vibrating magneticfields might be one candidate to explain the observed very high velocities for some solar wind particles.